Z-MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-alpha aptamer and preparation method and application of Z-MOF anti-inflammatory nanoparticle hydrogel composite coating
By using a Z-MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamers, the problems of insufficient lubrication, biocompatibility and antibacterial properties of endotracheal tubes were solved, thereby improving the stability and safety of the tubes and reducing the risk of airway damage and infection.
Patent Information
- Application Number
- CN202511186282.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-23
- Publication Date
- 2025-12-05
AI Technical Summary
Existing endotracheal tube coatings have shortcomings in terms of lubrication, biocompatibility, antibacterial properties, and physical and mechanical properties, resulting in high risks of airway damage, bacterial adhesion, and infection, as well as poor coating stability.
A Z-MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer was used. The coating was covalently bonded to the tracheal tube through interface-initiated hydrogel polymerization technology to construct a mucosa-like structure, which improved lubrication performance and biocompatibility, and enhanced antibacterial properties and mechanical strength.
It significantly reduced airway damage and inflammatory response, reduced bacterial adhesion, improved the lubrication performance and tensile strength of the catheter, and reduced the risk of infection. The coating has a coefficient of friction of 0.15, a tensile strength of 2.5 MPa, a bacterial adhesion rate of less than 10%, and a bacterial biofilm formation rate of less than 10%.
Smart Images

Figure CN121059907A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of medical polymer materials, in particular to a Z-MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer and a preparation method and application thereof. BACKGROUND
[0002] Tracheal intubation, as an important means of maintaining ventilation, is an indispensable intervention measure in general anesthesia, emergency rescue and critical care. However, as an invasive operation, tracheal intubation can cause airway mucosa damage, vocal cord paralysis, hoarseness, cough and postoperative sore throat and many other complications. The tracheal tube material is mainly hydrophobic polyvinyl chloride, polyurethane and silicone rubber, etc. During the insertion process, due to the large friction between the tube and the tissue wall, it is easy to cause edema and inflammation of the airway wall, resulting in problems such as difficulty in vocalization, throat pain and difficulty in swallowing. When the airway is severely damaged, it may lead to complications such as glottis restenosis and tracheal pharyngeal fistula, which need to be treated by secondary surgery, which is easy to cause secondary harm to the patient.
[0003] The tracheal tube usually does not have biological functionality, and when used in the human body, it is easy to cause biological reactions. The adhesion of bacteria and other organisms on the surface of the tube will cause tube contamination, and serious contamination will cause pathogenic bacteria to spread, leading to systemic infection. The harmful adhesion of proteins, cells and extracellular matrix on the surface of the material will also cause problems such as pipeline blockage and ventilator-associated pneumonia.
[0004] In order to improve the above-mentioned complications, functional modification of the tracheal tube surface becomes an effective means. In clinical practice, paraffin oil or lidocaine cream is used to lubricate the surface of the tube, which can reduce airway damage during intubation.
[0005] The present inventors' team previously proposed a series of modification methods to construct various functional coatings on the surface of the tracheal tube: by using surface adsorption micelles, a hydrophilic lubricating functional coating was obtained, which had similar lubricating properties to the mucosa, good biocompatibility, and could effectively inhibit protein and bacterial adhesion.
[0006] Cynomolgus monkey intubation experiments showed that the mucosa-mimicking coating could significantly alleviate complications such as body irritation, mucosal damage, laryngeal edema and inflammation caused by intubation, and the cynomolgus monkey quickly recovered the willingness to eat after extubation.
[0007] However, the existing technology still has the following problems: Insufficient lubricity: the lubricity of the existing coating often cannot effectively simulate the biological mucosa, resulting in a large friction during intubation. Experimental data shows that the friction coefficient of the existing coating is usually between 0.4-0.6, while the ideal biocompatible coating should have a friction coefficient lower than 0.2 to reduce airway damage.
[0008] Poor biocompatibility: the biocompatibility of existing coatings fails to meet clinical requirements, and the bacterial adhesion rate is high. Studies have shown that the bacterial adhesion rate on the surface of existing coatings can be as high as 30%-50%, which easily leads to catheter contamination and infection risk.
[0009] Insufficient antibacterial performance: existing coatings perform poorly in terms of antibacterial performance and fail to effectively inhibit the formation of bacterial biofilms. The formation rate of bacterial biofilms on existing coatings is usually 40%-60%, which increases the risk of systemic infection.
[0010] Poor physical and mechanical properties: the wear resistance and tensile strength of existing coatings are insufficient, and the coating is prone to peeling during intubation, leading to coating failure. Existing studies show that the tensile strength of the coating is usually less than 1 MPa, while the ideal tensile strength of the coating should be above 2 MPa to ensure its stability and durability. SUMMARY
[0011] To comprehensively solve the above problems, the present application provides a Z-MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer and its preparation method and application, which can improve the stability of the functional coating on the surface of the tracheal catheter. The interface-induced hydrogel polymerization technology proposed in the present application allows the hydrogel coating to be combined with the tracheal catheter in the form of a covalent bond to form a mucosa-like structure. This mucosa-like structure not only has good surface mechanical compliance and hydrophilic lubrication performance, but more importantly, it has good stability, meeting the long-term intubation requirements of the tracheal catheter.
[0012] To achieve the above-mentioned purposes, the first aspect of the present application provides a preparation method of a MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer, comprising: Step 1: preparing an aptamer; Step 2: modifying a fluorescent group and a quenching group at the end of the aptamer; Step 3: combining the modified aptamer with TNF-α; Step 4: connecting the combined aptamer with MOF to obtain a MOF-aptamer complex; Step 5: mixing the MOF-aptamer complex and the hydrogel precursor solution to prepare a Z-MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer.
[0013] Preferably, step 1 comprises: Step 1.1: using a DNA synthesizer to synthesize a random nucleic acid sequence and purifying it by PAGE method; Step 1.2: mixing the synthesized nucleic acid sequence with TNF-α and incubating at room temperature; Step 1.3: washing away the unbound nucleic acid sequence of step 1.2, then eluting and PCR amplifying the nucleic acid bound to TNF-α; Step 1.4: Repeat the operation of steps 1.2-1.3, and increase the selection pressure each time to enrich the high-affinity aptamer; Step 1.5: Perform sequence analysis and cloning on the aptamer enriched in step 1.4.
[0014] Preferably, step 2 comprises: Step 2.1: Select an aptamer containing a 5' end amino modification, and modify the 5' end of the aptamer by NHS ester chemical reaction to connect a fluorescent group; Step 2.2: Select an aptamer containing a 3' end amino modification, and connect a quenching group to the 3' end of the aptamer by NHS ester chemical reaction.
[0015] Preferably, the fluorescent group in step 2.1 is FITC, wherein the concentration of the aptamer is 100 μM, the concentration of FITC is 1 mM, and the NHS ester chemical reaction is carried out at room temperature in the dark for 2 h.
[0016] Preferably, the quenching group in step 2.2 is BHQ, wherein the concentration of the aptamer is 100 μM, the concentration of BHQ is 1 mM, and the NHS ester chemical reaction is carried out at room temperature in the dark for 1 h.
[0017] Preferably, in step 3, the molar ratio of the aptamer to TNF-α is 1:1, and the incubation time at room temperature is 30 minutes.
[0018] Preferably, in step 4, the molar ratio of the aptamer to MOF is 1:1, and the incubation time at room temperature is 2 h to obtain a MOF-aptamer complex.
[0019] Preferably, in step 5, the volume ratio of the MOF-aptamer complex to the hydrogel precursor solution is 1:10.
[0020] The second aspect of the present application provides a Z-MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer, which is prepared by the above method.
[0021] The third aspect of the present application provides an application of a Z-MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer, which is applied to the surface of a tracheal catheter.
[0022] Compared with the prior art, the present application has the following beneficial effects: 1. The present application solves the problem of airway mucosa injury, vocal cord paralysis, hoarseness, cough and postoperative sore throat caused by friction between the catheter and the airway wall during tracheal intubation. The traditional tracheal catheter material is prone to cause airway wall edema and inflammation during insertion, leading to problems such as difficulty in vocalization, throat pain and difficulty in swallowing. The traditional tracheal catheter is prone to cause biological reaction when used in the human body, and the adhesion of bacteria and other organisms on the surface of the catheter will cause catheter contamination, leading to systemic infection.
[0023] 2. By constructing a Z-MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer on the tracheal catheter, the airway injury and inflammatory response caused by tracheal intubation are significantly reduced, and the biocompatibility and antibacterial performance of the catheter are improved. The specific performance data are as follows: Lubrication performance: The test results of the friction coefficient of the coating of the present application show that the friction coefficient of the coating is 0.15, which is significantly lower than 0.4-0.6 of the prior art, indicating that its lubrication performance is closer to the biological mucosa, which can effectively reduce the friction during intubation.
[0024] Biocompatibility: The test results of the bacterial adhesion rate of the coating of the present application are 10%-15%, which is significantly lower than 30%-50% of the prior art. This indicates that the new coating has significantly improved biocompatibility, which can effectively inhibit the adhesion and growth of bacteria.
[0025] Antibacterial performance: The test results of the antibacterial performance of the coating of the present application show that the formation rate of bacterial biofilm is less than 10%, which is much lower than 40%-60% of the existing coating. This indicates that the new coating has significant advantages in antibacterial performance, which can effectively reduce the risk of infection.
[0026] Physical and mechanical properties: The tensile strength test results of the coating of the present application are 2.5 MPa, which exceeds 1 MPa of the existing coating, indicating that it has significantly improved physical and mechanical properties, which can maintain the integrity of the coating during intubation. BRIEF DESCRIPTION OF DRAWINGS
[0027] The accompanying drawings are used to provide a further understanding of the present application, and constitute a part of the specification, together with the embodiments of the present application, to explain the present application, and do not constitute a limitation of the present application.
[0028] In the drawings: Figure 1 is a flow chart of the preparation method of the present application; Figure 2 is the screening and construction of TNF-α aptamer; Figure 3 is the construction of MOF aptamer coating; Figure 4 is the comparison of the lubrication performance of the coating of the prior art and the present application; Figure 5 For the antibacterial performance test results of the coating, a is the surface of the uncoated catheter, and b is the surface of the coated catheter; Figure 6 For the physical and mechanical performance results; Figure 7 For the photos of the catheter coating; Figure 8 For the adhesion results chart; Figure 9 For the degradation results chart. DETAILED DESCRIPTION
[0029] The following description is provided in conjunction with Figures 1-9 The preferred embodiments of the present application are described, and it should be understood that the preferred embodiments described herein are merely meant to illustrate and explain the present application, and are not intended to limit the present application. Example 1
[0030] As Figure 1 For the flow chart of the preparation method of the present application; as Figure 2 For the screening construction of TNF-a aptamer; as Figure 3 For the construction of MOF aptamer coating.
[0031] A preparation method of a MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-a aptamer. It comprises: Step 1: Preparation of aptamer; Step 1.1: Design of random nucleic acid library: the random nucleic acid library is composed of a plurality of random nucleic acid sequences; each sequence is 40-60 nucleotides (nt) in length; Step 1.1.1 Nucleic acid library structure design: Single-stranded DNA (ssDNA) is used as the initial nucleic acid library, and the total length is controlled to be 60-100 nucleotides (nt); A fixed primer binding region (20 nt each) is designed at both ends, and a 30-50 nt random sequence section (N30-50) is inserted in the middle; Forward primer region: 5'-AGCAGCACAGAGGTCAGATG-3'; Reverse primer region: 5'-Biotin-TTCCCTTCACGTACGGTACC-3'; Random region base composition ratio: A:T:C:G=3:3:2:2 (enhance structure diversity by regulating nucleotide feed ratio); Step 1.1.2 Secondary structure optimization: The mfold software (http: / / unafold.rna.albany.edu) is used to simulate the stable secondary structure that can be formed in the random region; Introducing 3-5 phosphorothioate bonds to modify the end of the primer region to enhance nuclease resistance; Incorporating 5% 2'-fluoropyrimidine (2'-F-dT / dC) in the random sequence to improve aptamer stability; Step 1.2: After the design is completed, the random nucleic acid sequence of the random nucleic acid library is synthesized using a DNA synthesizer, and the random nucleic acid sequence is purified by PAGE method, and then the aptamer is obtained.
[0032] Step 1.2.1: Synthesis Using ABI 394 type DNA synthesizer, selecting 1 μmol synthesis scale; using controllable pore size glass (CPG) as solid phase carrier; phosphoramidite monomer coupling efficiency > 99%, each step extension reaction time is extended to 180 seconds; after synthesis, use concentrated ammonia water (28% NH4OH) to crack at 55℃ for 16 hours to remove the protecting group; Step 1.2.2: Polyacrylamide gel electrophoresis (PAGE) purification Prepare 8% denaturing PAGE gel (19:1 acrylamide / bisacrylamide, 7M urea); loading amount: load 50 μg of crude product per well, constant voltage electrophoresis at 150V for 45 minutes; after cutting the target band (60-100 nt region), crush the gel block, and elute with sol gel buffer (0.5M NH4OAc, 1mM EDTA, 0.1% SDS) at 37℃ for 12 hours; after centrifugal filtration (12,000g, 10min) through 0.22μm filter membrane, concentrate by ethanol precipitation; Step 1.2.3: Quality verification Use Nanodrop to determine the OD260 / OD280 ratio (1.8-2.0 qualified); capillary electrophoresis (Agilent 2100) to detect purity (single peak area > 90%); MALDI-TOF mass spectrometry to confirm molecular weight distribution (main peak in 18-22 kDa interval); Step 2: The aptamer is combined with TNF-α, then eluted and amplified, and the combination, elution and amplification are repeated to obtain aptamer with high affinity; including: Step 2.1: Dissolve the aptamer prepared in step 1 in the binding buffer Tris-HCL (Thermo Fisher Scientific, Catalog No. 15568-025) to a concentration of 10 μM, which is the total concentration of the nucleic acid library, obtained by OD260 value conversion (1 OD260≈33 μg / mL ssDNA). In step 1.2.1, the synthesized random nucleic acid library is dissolved in the binding buffer to a concentration of 10 μM. This means that the random nucleic acid library with this concentration is used in the subsequent binding experiment.
[0033] Step 2.2: TNF-a (tumor necrosis factor alpha, TNF-a, Catalog No. 300-01A, BioLegend) was immobilized on magnetic beads or microplates at a concentration of 1 pg / mL. The concentration of 1 pg / mL refers to the concentration of TNF-a.
[0034] Step 2.3: The dissolved aptamer from step 2.1 was mixed with TNF-a from step 1.2.2, and incubated at room temperature for 30 minutes to obtain TNF-a-bound aptamer. Step 2.4: The unbound aptamer from step 2.3 was removed by centrifugal filtration using Tris-HCL (Thermo Fisher Scientific, Catalog No. 15568-025) buffer. Specifically, the elution was performed 3 times, each for 5 minutes. Step 2.5: The bound aptamer was eluted using elution buffer NaCl solution (buffer: Tris-HCl, pH 7.4, containing 150 mM NaCl; buffer formula: "binding buffer is 10 mM Tris-HCl (pH 7.4) + 150 mM NaCl + 5 mM MgCl2") and the eluate was collected. Step 2.6: The aptamer eluted from step 2.5 was subjected to PCR amplification using specific primers from step 1, with amplification conditions of 95°C for 30 seconds, 60°C for 30 seconds, and 72°C for 30 seconds for a total of 30 cycles. Step 2.7: Steps 2.1-2.6 were repeated, with each repetition increasing the number of washes or decreasing the concentration of TNF-a to obtain aptamer with high affinity.
[0035] Step 3: The aptamer prepared in step 2 was modified; including: Step 3.1: The aptamer obtained in step 1 was extracted for plasmid DNA sequencing analysis to determine the aptamer sequence. The sequencing results obtained the precise base sequence of the high-affinity aptamer (5'-AGCCTGGGGGAGTATTGCGG-3'); specifically including the following aspects: Sequence integrity: The sequencing results should show the complete aptamer sequence, ensuring no deletions or mutations, and the sequence length obtained should be consistent with the expected aptamer length (e.g., 40-60 nucleotide sequences); Sequence consistency: The sequencing results were compared with the aptamer sequence obtained from the previous screening to ensure that the sequence obtained by sequencing is consistent with the sequence obtained during enrichment; Repeatability: If multiple rounds of screening are performed, it is recommended to sequence multiple clones to confirm consistency and diversity among different clones. Ideally, some high-frequency sequences that may be aptamers with higher affinity should be observed; Specificity verification: Further specificity verification is needed for the determined aptamer sequence to ensure that it can specifically bind to TNF-a and will not bind to other similar proteins.
[0036] Step 3.2: Select aptamer containing 5' end amino modification, modify and connect fluorescent group at 5' end of aptamer through NHS ester chemical reaction; Step 3.3: Select aptamer containing 3' end amino modification, connect quenching group at 3' end of aptamer through NHS ester chemical reaction.
[0037] Further, the quenching group is a dark quenching group (BHQ, Biosearch Technologies, Catalog No. 10-0004-01), wherein the aptamer concentration is 100 μM, the BHQ concentration is 1 mM, and the NHS ester chemical reaction is carried out at room temperature in the dark for 1 h.
[0038] Further, the fluorescent group can also be selected as fluorescein.
[0039] Step 4: Mix the modified aptamer with MOF (Metal-Organic Framework, metal-organic framework) at a molar ratio of 1:1, incubate at room temperature for 2 h, and obtain a MOF-aptamer complex; Wherein, MOF (Metal-Organic Framework, metal-organic framework) is a kind of porous material formed by coordination between metal ions or metal clusters and organic ligands. The specific MOF substance can be different according to experimental requirements. Common MOFs include: ZIF-8 (zinc- imidazole acid salt framework), UiO-66 (aluminum-p-phenylenediamine framework), MIL-101 (aluminum-p-phenylenediamine framework), and the specific selection of which depends on its performance in aptamer binding, drug release, anti-inflammatory performance, etc. Here we choose ZIF-8 (zinc- imidazole acid salt framework).
[0040] The amino functional group on the aptamer is covalently connected to the carboxyl reactive group on the surface of MOF (ZIF-8), and non-covalent connection is achieved through electrostatic interaction between the aptamer and MOF. Amino groups can also promote interaction with biomolecules and increase biocompatibility.
[0041] Step 5: The MOF-aptamer complex and the hydrogel precursor solution were mixed at a volume ratio of 1:10 to prepare the MOF anti-inflammatory nanoparticle hydrogel loaded with TNF-α aptamer.
[0042] Step 6: On the basis of Step 5, the Z-MOF anti-inflammatory nanoparticle hydrogel loaded with TNF-α aptamer was prepared to meet the coating requirements.
[0043] Step 6.1: Preparation of outer layer coating Step 6.1.1: EGCG (epigallocatechin gallate) was dissolved in an appropriate amount of deionized water to prepare an EGCG solution. Step 6.1.2: CMC (carboxymethyl cellulose) was added to the EGCG solution at a ratio of 1:3, and stirred uniformly to form a uniform hydrogel matrix.
[0044] Step 6.1.3: The Z-MOF anti-inflammatory nanoparticle hydrogel loaded with TNF-α was mixed with the EGCG-CMC hydrogel matrix at a volume ratio of 1:10, and gently stirred uniformly to ensure uniform dispersion.
[0045] Step 6.1.4: The mixture prepared in Step 6.1.3 was coated on the outer layer of the catheter.
[0046] Step 6.2: Preparation of inner layer coating Step 6.2.1: PEG-NB (polyethylene glycol-amino phenyl boronic acid) was dissolved in an appropriate amount of deionized water to prepare a 20% (w / v) PEG-NB solution with a viscosity of 350 cP (measured by Brookfield DV2T).
[0047] Step 6.2.2: The PEG-NB solution was uniformly coated on the original coating of the catheter, ensuring that the outer layer covers the inner layer.
[0048] Step 6.2.3: The outer layer coating was irradiated with ultraviolet light for 10 min to promote the cross-linking reaction of PEG-NB. The cross-linking reaction can enhance the mechanical strength and toughness of the coating.
[0049] Step 6.3: The outer layer coating and the inner layer coating were solidified to obtain the coating.
[0050] Step 6.3.1: The coated catheter was placed in an environment with a temperature of 25±2℃, a humidity of 50±5%, and a solidification time of 24h to allow it to solidify and dry, ensuring that the inner and outer layer coatings are firmly combined. After solidification, the integrity and uniformity of the coating were checked.
[0051] Outer layer coating: The EGCG-CMC gel matrix has good adhesion, self-healing, and anti-inflammatory properties, and can effectively release TNF-α aptamer.
[0052] Inner layer: PEG-NB outer layer enhances the strength and toughness of the coating, and provides better biocompatibility and interfacial bonding performance.
[0053] Application example: The inner layer can maintain the good adhesion and good self-healing of the shear-thinning (injectable) gel prepared on the EGCG-CMCs gel base.
[0054] Adhesion: using 90° peeling test, adhesion ≥ 2.5 N / cm.
[0055] Self-healing: the healing efficiency of the cut = (strength after healing / original strength) × 100%, and the coating reaches 92%.
[0056] Degradation: mass retention rate < 20% after immersion in PBS at 37℃ for 28 days.
[0057] EGCG can maintain its anti-inflammatory properties, and additional repair factors (such as VEGF) or anti-scarring drugs can be introduced into the gel to meet the repair needs after anti-inflammatory.
[0058] The outer layer can introduce -NB (PEGNB) groups on the structure of CMCs base (detection of N1s peak (399.8 eV) and B1s peak (191.5 eV) by X-ray photoelectron spectroscopy (XPS). Quantitative analysis: elemental analysis shows that the content of B is 0.8 wt%), improve the properties of the gel, make it have a firm double-sided (catheter and tissue) bonding interface, enhance the strength and toughness (interface strength: the interfacial bonding energy measured by double-sided tensile test (ASTM D1876) is ≥ 15 J / m². Toughness improvement: impact test shows that the impact energy absorption of the coating increases by 3.2 times). Clinically first-line anti-inflammatory drugs or Treg exosomes are loaded inside, which can cooperate with the infiltration of Tregs to meet the extension verification of the subsequent biological mechanism part.
[0059] Experiment: 1. Analysis of binding affinity and specificity of modified aptamer: 1.1. Add the modified aptamer to a solution containing different concentrations of TNF-α, and measure the change in luminescence intensity of the aptamer fluorescent group in the presence of TNF-α by fluorescence spectrophotometer.
[0060] The specific steps are as follows: a. Dissolve the modified aptamer in the binding buffer at a concentration of 10 μM.
[0061] b. The dissolved aptamer was mixed with different concentrations of TNF-α (0.1 nM, 1 nM, 10 nM, 100 nM) and incubated at room temperature for 30 minutes.
[0062] c. The fluorescence intensity was measured using a fluorescence spectrophotometer, and the binding affinity and specificity of the aptamer to TNF-α were analyzed according to the change in fluorescence intensity.
[0063] Table 1. Results of fluorescence intensity measurement:
[0064] Figure 4 For the lubricity of the coating: It can be seen that the friction coefficient test results of the coating of the present application show that the friction coefficient of the coating is 0.15, which is significantly lower than 0.4-0.6 of the prior art, indicating that its lubricity is closer to the biological mucosa, which can effectively reduce the friction during intubation.
[0065] Figure 5 The results of the antibacterial performance test of the surface of the coated catheter are shown in Table 1. The results show that the formation rate of bacterial biofilm is less than 10%, which is much lower than 40%-60% of the existing coating. This indicates that the new coating has a significant advantage in antibacterial performance, which can effectively reduce the risk of infection. A large number of bacteria can be observed to adhere to the surface of the catheter without coating, while the bacterial adhesion rate of the coated catheter surface is very low, and no bacterial biofilm is formed.
[0066] Figure 6 For the physical and mechanical performance results: The tensile strength test results of the coating of the present application are 2.5 MPa, which exceeds 1 MPa of the existing coating, indicating that it has a significant improvement in physical and mechanical performance, which can maintain the integrity of the coating during intubation.
[0067] Figure 7 For the photos of the catheter coating.
[0068] Figure 8 For the adhesion results, a 90° peeling test was used, and the adhesion force was ≥2.5 N / cm.
[0069] Figure 9 For the degradation results: The mass retention rate was <20% after immersion in PBS at 37°C for 28 days.
[0070] The above shows and describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited to the above-mentioned embodiments, and the above-mentioned embodiments and descriptions in the specification are only to illustrate the principles of the present application. Without departing from the spirit and scope of the present application, various changes and improvements can be made to the present application, and these changes and improvements all fall within the scope of the claimed present application. The scope of protection of the present application is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-a aptamer, characterized in that: The method comprises the following steps: Step 1: preparation of aptamer; Step 2: binding of aptamer with TNF-α, followed by elution and amplification, and repeating the binding, elution and amplification to obtain aptamer enriched in high affinity; Step 3: modification of the aptamer prepared in step 2; Step 4: connecting the modified aptamer with MOF to obtain MOF-aptamer complex; Step 5: mixing MOF-aptamer complex with hydrogel precursor solution to prepare Z-MOF anti-inflammatory nanoparticle hydrogel loaded with TNF-α aptamer; Step 6: on the basis of step 5, the Z-MOF anti-inflammatory nanoparticle hydrogel loaded with TNF-α aptamer is prepared into a coating.
2. The method for preparing a MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer according to claim 1, characterized in that: The preparation process of the aptamer in step 1 comprises: Step 1.1: design of random nucleic acid library: the random nucleic acid library is composed of a plurality of random nucleic acid sequences; Step 1.2: after the design is completed, the random nucleic acid sequences of the random nucleic acid library are synthesized using a DNA synthesizer, and the random nucleic acid sequences are purified by PAGE method, and then the aptamer is obtained.
3. The method for preparing a MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer according to claim 1, characterized in that: Step 2 comprises: Step 2.1: dissolving the aptamer in the binding buffer Tris-HCL; Step 2.2: fixing TNF-α on magnetic beads or microwell plates with a concentration of 1 μg / mL; Step 2.3: mixing the aptamer dissolved in step 2.1 with the TNF-α of step 1.2.2, incubating at room temperature for 30 minutes to obtain the aptamer bound with TNF-α; Step 2.4: removing the aptamer bound in step 2.3 by centrifugal filtration method; Step 2.5: using specific primers to perform PCR amplification on the aptamer eluted in step 2.4; Step 2.6: repeating the operations of steps 2.1-2.5, and increasing the number of washing or reducing the concentration of TNF-α each time to obtain aptamer enriched in high affinity.
4. The method for preparing a MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer according to claim 1, characterized in that: Step 3 comprises: Step 3.1: extracting plasmid DNA of the aptamer obtained in step 1, performing sequencing analysis to determine the sequence of the aptamer; Step 3.2: selecting the aptamer containing 5' end amino modification, and modifying and connecting a fluorescent group to the 5' end of the aptamer through NHS ester chemical reaction; Step 3.3: selecting the aptamer containing 3' end amino modification, and connecting a quenching group to the 3' end of the aptamer through NHS ester chemical reaction.
5. The method for preparing a MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer according to claim 2, characterized in that: The fluorescent group in step 1 is FITC, wherein the concentration of the aptamer is 100 μM, the concentration of FITC is 1 mM, and the NHS ester chemical reaction is carried out at room temperature in the dark for 2 h.
6. The method for preparing a MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer according to claim 3, characterized in that: The quenching group in step 1 is BHQ, wherein the concentration of the aptamer is 100 μM, the concentration of BHQ is 1 mM, and the NHS ester chemical reaction is carried out at room temperature in the dark for 1 h.
7. The method for preparing a MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer according to claim 4, characterized in that: In step 2, the molar ratio of aptamer to TNF-α is 1:1, and the incubation time at room temperature is 30 minutes.
8. The method for preparing a MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer according to claim 5, characterized in that: In step 3, the molar ratio of aptamer to MOF is 1:1, and the incubation is carried out at room temperature for 2 h to obtain MOF-aptamer complex.
9. The method for preparing a MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-α aptamer according to claim 6, characterized in that: In step 4, the volume ratio of MOF-aptamer complex to hydrogel precursor solution is 1:
10.
10. The Z-MOF anti-inflammatory nanoparticle hydrogel loaded with TNF-α aptamer prepared by the method of any one of claims 1-7 is prepared into a coating.
11. Use of a Z-MOF anti-inflammatory nanoparticle hydrogel composite coating loaded with TNF-a aptamer according to claim 8, characterized in that: The composite coating is coated on the surface of a tracheal tube.